Assessment of Bottled Drinking Water Quality in Baghdad Local Market by Some Chemical and Biological Parameters - Kadhim, Ahmed Kh; Salih, Noor Y; Hamad, Sabah O (Al-Nahrain Journal of Science, 2018)
The aim of this work is to study different parameters of bottled drinking water that affect the health of people of Baghdad city. To perform this target, seventeen bottled samples were collected from local markets which were different bottles size and trade markets. The samples were analyzed physical, chemical and biological factors that influence water quality of the bottled water. The physical and chemical tests of bottled water showed that the mean value of pH ranged from 6.96-8.5, Total Dissolved Solids (TDS) 8-166 ppm, Total Hardness (TH) 22-178 ppm, Calcium (Ca++) 0.0-35 ppm, Magnesium (Mg++) 0.0-30 ppm, Chloride (Cl-) 0.0-27 ppm, sodium (Na+) 0.0-25 ppm, potassium (K+) 0.0-4.5 ppm, Electrical Conductivity (Ec) 16-332 µs/cm. All samples were within the permissible limits for Iraqi criteria and standards for bottled water. The biological parameters include: total plate count, total coliform, fecal coliform, E.coli and yeast& fungi. The failure percentages of samples were 23.5, 11.7, 11.7, 11.7 and 11.7% respectively.